Efectividad de la intervención de enfermería y ansiedad en pacientes prequirúrgicos en un hospital del tercer nivel de la ciudad de Iquitos 2022 - Menéndez Holguín, Wendy Stephanie (2023)
The objective of the research study was to determine the effectiveness of nursing intervention and anxiety in pre-surgical patients in a tertiary hospital in the city of Iquitos 2022. The method was quantitative, non-experimental, cross-sectional, correlational and intervention design, the population consisted of 124 pre-surgical patients in a third level hospital in the city of Iquitos and the sample consisted of 94 patients; the technique used for data collection was the interview and the intervention, as one instrument is standardised and the other was validated, the instruments were: Spielberger's state anxiety scale (validity 0.98% and reliability 0.90%- 0.93%) and nursing intervention programme (validity 88.10%). The study determined that the level of anxiety in pre-surgical patients before nursing intervention is high anxiety (62.8%) and moderate anxiety (37.2%) and low anxiety (0.0%); and the level of anxiety in pre-surgical patients after nursing intervention is moderate anxiety (67.0%), high anxiety (33.0%) and low anxiety (0.0%). By applying the Wilcoxon Ranks Z= - 4.427; p=0.000, it was found that the nursing intervention had a positive effect on anxiety. In conclusion, by applying the Spielberger state anxiety sub - scale instrument, it was determined that the nursing intervention is effective in pre-surgical patients with anxiety in a third level hospital in the city of Iquitos 2022.